Analysis of caesarean section using Robson’s ten group classification in a tertiary care centre - Ambat, Gopika; Jain, Madhu; Anuranjani, Lavanya; Srivastava, Yashi; Thakur, Anita; Priya, Prerna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Caesarean section is the most common obstetric operation that saves lives of countless mother and babies. In the past few decades, caesarean section rates have been continuously increasing worldwide. WHO declared that there is no justification for any region to have a caesarean section rate higher than 10-15% and added that CS rates higher than 10% is not associated with reduction in newborn and maternal mortality rates. In 2015, WHO proposed Robson classification as a global standard of assessing, monitoring comparing and auditing the determinants of caesarean sections rates. Methods: This Retrospective study was done in the department of Obstetrics and Gynecology, Heritage institute of medical Sciences, Varanasi. The study duration was from July 2021 to June 2022. Results: A total of 2039 cases underwent delivery during the study duration. The caesarean rate calculated was 46.3%. Group 5 (previous CS, single, cephalic, >37weeks) made the greatest contributor to total CS rate followed by Group 1 (nulliparous, single, cephalic, >37 weeks in spontaneous labor). 100% of women with abnormal lie (group 9) and 87.9% women with breech presentation underwent CS. Conclusions: The overall rate of Caesarean sections is on an increasing trend. Robson’s Group 5 and 1 were the major contributors to caesarean section in this study. RTGCS is a simple useful tool which is a starting point for meaningful analysis of CS both at facility level and across different facilities.